The Politics of Communal Feasting in Roman Macedonia - Ching-Yuan Wu (The 14th TACMRS International Conference, 2020)
The purpose of this paper is to take a diachronic approach and survey the pre-Roman and Roman evidence of communal feasting in Macedonia, in order to understand how such form of social action changed after a well-established form executed by the Macedonian monarchy came under the challenges posed by the years of turmoil following Rome's conquest. The basic premise of this paper is that feasting is a politically-embedded form of social occasion and naturally subject to manipulation. In turn, the scale of communal feasting would reflect different strategies of the manipulating parties, and in particular one can distinguish from the strongly aspirational type of communal feasting aimed at creating national and even sovereign symbolisms from the transactional types of communal feasting in which the host and the participants partake in the small-group manuvers of more limited socio-political implications. Evidence highlighted in this paper include the well-known Hagios Athanasios symposium frieze, the honorific inscription for Apollonios son of Apollonios from Kalindoia (SEG 35.744), and a sample of Macedonian inscriptions concerning local cultic associations and the Macedonian koinon.